Regulatory Harmonization in Indonesian Labor Law: The Principle of Lex Posterior Derogat Legi Priori and Outsourcing Regulations After Minister of Manpower Regulation No. 7 of 2026 - Turija Turija; Suandi Suandi; Nasaruddin Nasaruddin (Yayasan Sembilan Pemuda Indonesia, 2026)
The issuance of Minister of Manpower Regulation Number 7 of 2026 has introduced significant changes to Indonesia’s outsourcing regime and has raised concerns regarding its consistency with existing labor regulations. These developments have intensified debates on legal certainty and the appropriate methods for resolving conflicts among labor law provisions. This study examines the relevance of the principle of lex posterior derogat legi priori in addressing inconsistencies within the legal framework governing outsourcing practices in Indonesia. Using a normative legal research method, the study applies statutory, conceptual, and case-based approaches to analyze several key legal instruments, including the Manpower Law, the Job Creation Law, Constitutional Court Decision Number 168/PUU-XXI/2023, and Minister of Manpower Regulation Number 7 of 2026. The analysis demonstrates that the principle of lex posterior derogat legi priori cannot independently resolve regulatory conflicts. Its implementation must be complemented by the principle of lex superior derogat legi inferiori and supported through broader legislative harmonization efforts. The study also identifies persistent uncertainties concerning employment relationships, worker protection, and the allocation of legal responsibilities between outsourcing providers and user companies. Therefore, stronger regulatory harmonization, effective enforcement, and clear transitional arrangements are necessary to ensure legal certainty and a more balanced outsourcing system.